Transmedia educational narratives and the INAEP Method applied to Non-formal Education: The case of the transmedia comicbook El Bogotazo: reinicio de una ciudad - García Rojas, Maribel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This document presents the preliminary results, on an ongoing research that articulates educational transmedia narratives with the proposal of an emerging methodology called INAEP (Spanish initials for Investigate, Narrate, Elaborate, and Question). The text contemplates the reflections on observations made to a group of Scouts, boys and girls ages 10 to 14, located in the city of Bogotá, Colombia. The children were taught history in a non-formal educational environment through didactic materials developed under the bases of INAEP, in the light of which it is expected to evaluate their learning and the method’s applicability in different educational contexts.